Wilms' Tumor protein 1 and enzymatic oxidation of 5-methylcytosine in brain tumors: potential perspectives - Ramsawhook, Ashley; Ruzov, Alexey; Coyle, Beth (Frontiers Media, 2018)
The patterns of 5-methylcytosine (5mC) and its oxidized derivatives, 5-hydroxymethylcytosine, 5-formylcytosine, and 5-carboxylcytosine (5caC) are reportedly altered in a range of cancers. Likewise, Wilms’ Tumor protein 1 (WT1), a transcription factor essential for urogenital, epicardium, and kidney development exhibits aberrant expression in multiple tumors. Interestingly, WT1 directly interacts with TET proteins that catalyze the enzymatic oxidation of 5mC and exhibits high affinity for 5caC-containing DNA substrates in vitro. Here we review recent developments in the fields of Tet-dependent 5mC oxidation and WT1 biology and explore potential perspectives for studying the interplay between TETs and WT1 in brain tumors.